PERAN ORANG TUA DALAM UPAYA PENANGGULANGAN REMAJA PENGGUNA NARKOBA (STUDI KASUS DI JORONG TAPIAN NANTO, KECAMATAN SIJUNJUNG, KABUPATEN SIJUNJUNG) - Anggraini, Marisa; Yatim, Yenita; Yuhelna, Yuhelna (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
drug Abuse is a reality encountered within society. Nationally, the outbreak of drug abuse is not only carried out by adults, but also children who are still undergoing basic education are not spared from committing abuse. The purpose of this study was to find out and analyze the role of parents in efforts to overcome adolescent drug users (Case Study in Jorong Tapian Nanto, Sijunjung District, Sijunjung Regency). The theory used in this study is The theory of the functional social conflict is one of the conflict theories that was first introduced in 1956 through Lewis Coser's work entitled The functions of Social Conflict which was lifted from his doctoral dissertation. The results showed that the role of parents in efforts to overcome adolescent drug users is divided into 4, namely 1) the role of parents as motivators, 2) the role of parents as facilitators, 3) the role of parents as mediators, 4) the role of parents in dealing with the problem of addiction to addictive substances where in this study it was found that parents have performed all four roles well, but drug use by adolescents is due to the influence of friends. Peer. So although it can be supervised by parents, but outside the home, adolescent associations are difficult to supervise.